A national level survey on knowledge, attitude and practices among Indian nurses on viral hepatitis - Mini George; Tarika Sharma; Sarita Ahwal; Aayushi Rastogi; Akanksha Bansal (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Despite being preventable and treatable, viral hepatitis remains a major public health problem in India. In the line of their duties, nursing professionals are constantly at risk of infection. To combat viral hepatitis, it is essential to ascertain the level of knowledge, attitude, and practices among nursing professionals. MATERIALS AND METHODS: A descriptive cross-section study was conducted at a tertiary public hospital, as a nation-wide online survey after ethical clearance and participants' consent. A convenience sampling, from November 2021 to September 2022, yielded a total of 4532 nurses, nursing students and educators. A self-administered 62-item questionnaire on viral hepatitis with four sections: demographic details, knowledge (33-items), attitude (5-items), and practice (24-itmes) was prepared by expert panel and had a content validity and reliability >0.8. The scale was compiled onto the SurveyMonkey app, field tested before administration and widely circulated on email. RESULT: The response rate of the survey was 77%. Frequency, percentage, and the odds ratio (at 95% confidence interval) were analyzed on SPSS v22.0. Majority were females (87.1%) aged <30 years (60%) with <5 years' experience (57.8%). Almost equal number worked in public or private sector and was holders of diploma (44.5%) or degree (43.8%). Overall poor knowledge (85.3%), unfavorable attitude (86.2%), and unsafe practices (55.6%) were exhibited by nurses; 42.2% encountered needle stick injury last year and 49.8% had never checked Anti-HBs titer. In the event of needle stick injury, 74.78% cleansed with soap and water; used antiseptics or washes (33.5%), placed finger in mouth (5.10%), forced wound bleed (17.3%), scrub wound (17.54%), or apply bandage (12.58%). Multivariate analysis of factors influencing knowledge of viral hepatitis was educational qualification, designation, and type of health facility. CONCLUSION: As nursing professionals are constantly at risk, there is an urgent need to raise awareness about hepatitis, the post-exposure prophylaxis and vaccination status. Every healthcare facility should include training and capacity building for nurses about risk, prevention, transmission, and management of viral hepatitis, as an integral part of orientation and continuing education on-the-job; follow stringent policies; and set-up mechanisms for monitoring and follow up. Further, policymakers and statutory bodies need to ensure the standards of nursing practice and improve the health of nurses and their patients.